Evolution of local e-government maturity in Portugal - Gonçalo Paiva Dias (2014)
In this article we present the results of a website content analysis of all Portuguese municipalities performed in 2013. A three-dimensional maturity model was used to categorize e-government development. The results are compared with others obtained in 2010 in order to characterize local e-government evolution in Portugal. The main conclusion of this study is that, although the results of municipalities have globally improved between 2010 and 2013, the gap between municipalities to what respects e-government development is also growing. Indeed, a non-negligible percentage of municipalities worsened their results in this period.